Managing digital certificates across the enterprise - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2016)
This IBM Redbooks publication is the first in a series of five books that relate to the implementation and management of digital certificates that are based on a public key infrastructure. --
Number on resource description page: SG24833600. - "Security; z Systems.". - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed March 1, 2016)
Keywords: Internet -- Security measures; Data encryption (Computer science); Internet; Sécurité; Mesures; Chiffrement (Informatique); Internet; Security measures